2012
DOI: 10.1155/2012/426853
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Ensheathing Cell Tumor Arising from the Olfactory Mucosa

Abstract: We report a rare case of olfactory ensheathing cell tumor. A female presented a large soft mass extending medially to the olfactory cleft and laterally to the middle meatus in the left nasal cavity. Imaging studies confirmed a cystic mass extending superiorly into the frontal lobe, indicating that the tumor arouse from the olfactory mucosa. A subtotal resection was achieved through an endoscopic endonasal approach without operative complications. Immunohistochemically constituent cells were diffusely positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…In the present case, the radiological manifestations of the OECT were confusing, as a dural tail sign was evident on enhanced MRI and bone sclerosis and calcification were identified on computed tomography, which are similar to those observed with OGM (9). The differential diagnosis of tumors involving the extra-axial anterior cranial fossa, with or without bulging into the ethmoid sinus, should include OGM, OGS, OECT, Table II.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…In the present case, the radiological manifestations of the OECT were confusing, as a dural tail sign was evident on enhanced MRI and bone sclerosis and calcification were identified on computed tomography, which are similar to those observed with OGM (9). The differential diagnosis of tumors involving the extra-axial anterior cranial fossa, with or without bulging into the ethmoid sinus, should include OGM, OGS, OECT, Table II.…”
Section: Discussionsupporting
confidence: 59%
“…OECT may be treated surgically using the endoscopic transnasal approach or craniotomy. OECT has an extremely good prognosis, with a reported 2-year survival rate of 100% (2,(5)(6)(7)(8)(9)(10)(11). The present study reports the ninth case of OECT, which included confusing radiographic features, and presents a review of the literature.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…It is also necessary to differentiate these malignancies from common meningiomas in the anterior fossa (2). OECT was first identified as a distinct entity by Yasuda et al in 2006 (1), and only seven cases have been reported to date (1,(3)(4)(5)(6)(7)(8). Therefore, little information is available with regard to the clinical, radiological and immunohistochemical characteristics of OECTs (5).…”
Section: Introductionmentioning
confidence: 99%